3(x-1)-2x/5=5(x-3)/6?
Soluções para a tarefa
Respondido por
0
3(x-1)-2x/5=5(x-3)/6
multiplicamos
3x-3-2x/5=5x-15/8
x-3/5=5x-15/6
x-3/5 - 5x+15/6=0
(mmc=30)
30x-90/30 -150x+450/30=0
-120x+360/30
dividindo os valores por 30
-4x+12=0
-4x= -12
x= -12/-4
x= +3
Respondido por
1
Segue Amigo(a)
3(x-1)-2x/5=5(x-3)/6
multiplicamos
3x-3-2x/5=5x-15/8
x-3/5=5x-15/6
x-3/5 - 5x+15/6=0
(mmc=30)
30x-90/30 -150x+450/30=0
-120x+360/30
dividindo os valores por 30
-4x+12=0
-4x= -12
x= -12/-4
x= +3
Perguntas interessantes
História,
9 meses atrás
Artes,
9 meses atrás
Matemática,
1 ano atrás
Contabilidade,
1 ano atrás
Biologia,
1 ano atrás
Geografia,
1 ano atrás